Towards clinical management of traumatic brain injury: a review of models and mechanisms from a biomechanical perspective - Dhananjay R. Namjoshi; Craig Good; Wai Hang Cheng; William Panenka; Darrin Richards; Peter A. Cripton; Cheryl L. Wellington (The Company of Biologists, 2013)
Traumatic brain injury (TBI) is a major worldwide healthcare problem. Despite promising outcomes from many preclinical studies, the failure of several clinical studies to identify effective therapeutic and pharmacological approaches for TBI suggests that methods to improve the translational potential of preclinical studies are highly desirable. Rodent models of TBI are increasingly in demand for preclinical research, particularly for closed head injury (CHI), which mimics the most common type of TBI observed clinically. Although seemingly simple to establish, CHI models are particularly prone to experimental variability. Promisingly, bioengineering-oriented research has advanced our understanding of the nature of the mechanical forces and resulting head and brain motion during TBI. However, many neuroscience-oriented laboratories lack guidance with respect to fundamental biomechanical principles of TBI. Here, we review key historical and current literature that is relevant to the investigation of TBI from clinical, physiological and biomechanical perspectives, and comment on how the current challenges associated with rodent TBI models, particularly those involving CHI, could be improved.